Inter-Comparison Campaign of Solar UVR Instruments under Clear Sky Conditions at Reunion Island (21 • S, 55 • E) - (:unkn) unknown (My University, 2020)
Measurement of solar ultraviolet radiation (UVR) is important for the assessment of potential beneficial and adverse impacts on the biosphere, plants, animals, and humans. Excess solar UVR exposure in humans is associated with skin carcinogenesis and immunosuppression. Several factors influence solar UVR at the Earth's surface, such as latitude and cloud cover. Given the potential risks from solar UVR there is a need to measure solar UVR at different locations using effective instrumentation. Various instruments are available to measure solar UVR, but some are expensive and others are not portable, both restrictive variables for exposure assessments. Here, we compared solar UVR sensors commercialized at low or moderate cost to assess their performance and quality of measurements against a high-grade Bentham spectrometer. The inter-comparison campaign took place between March 2018 and February 2019 at Saint-Denis, La Réunion. Instruments evaluated included a Kipp&Zonen UVS-E-T radiometer, a Solar Light UV-Biometer, a SGLux UV-Cosine radiometer, and a Davis radiometer. Cloud fraction was considered using a SkyCamVision all-sky camera and the Tropospheric Ultraviolet Visible radiative transfer model was used to model clear-sky conditions. Overall, there was good reliability between the instruments over time, except for the Davis radiometer, which showed dependence on solar zenith angle. The Solar Light UV-Biometer and the Kipp&Zonen radiometer gave satisfactory results, while the low-cost SGLux radiometer performed better in clear sky conditions. Future studies should investigate temporal drift and stability over time.
Keywords: African Research